On the Influence of the Solar Wind on the Propagation of Earth-impacting Coronal Mass Ejections - Kumar, Sandeep; Srivastava, Nandita; Gopalswamy, Nat; Dash, Ashutosh (The Astrophysical journal, 2024)
Coronal mass ejections (CMEs) are subject to changes in their direction of propagation, tilt, and other properties as they interact with the variable solar wind. We investigated the heliospheric propagation of 15 Earth-impacting CMEs observed during 2010 April to 2018 August in the field of view (FOV) of the Heliospheric Imager (HI) on board the STEREO. About half of the 15 events followed self-similar expansion up to 40 R ⊙ . The remaining events showed deflection either in latitude, longitude, or a tilt change. Only 2 events showed significant rotation in the HI1 FOV. We also use toroidal and cylindrical flux rope fitting on the in situ observations of interplanetary magnetic field and solar wind parameters to estimate the tilt at L1 for these 2 events. Although the sample size is small, this study suggests that CME rotation is not very common in the heliosphere. We attributed the observed deflections and rotations of CMEs to a combination of factors, including their interaction with the ambient solar wind and the influence of the ambient magnetic field. These findings contribute to our understanding of the complex dynamics involved in CME propagation and highlight the need for comprehensive modeling and observational studies to improve space weather prediction. In particular, HI observations help us to connect observations near the Sun and near the Earth, improving our understanding of how CMEs move through the heliosphere.